AN ANALYSIS OF GENDER REPRESENTATION IN I LOVE JAKARTA, AN ELEMENTARY TEXTBOOK - Junita Junita; Joseph Bryant T. Pasaribu T. Pasaribu; Angela Novianita Vidiastya (Universitas Bunda Mulia, 2022)
Klein (1985) believes that appropriate gender-unbiased material mostly gives students the chance to accommodate more compliant mindsets towards gender roles. This study was conducted to observe the way genders are represented in local elementary textbooks in Indonesia, especially the textbook entitled